EVIDENCE FOR THE TRANSITION ZONE ORIGIN OF SOME [MG,FE]O INCLUSIONS IN DIAMONDS - Gasparik T. (My University, 2000)
Inclusions of [Mg,Fe]O (fPc, ferropericlase, magnesiowüstite) were found in natural diamonds from several localities worldwide. fPc is typically absent from upper-mantle assemblages, but expected to be common in the lower mantle in assemblages with [Mg,Fe]SiO3 perovskite. This led to proposals that the inclusions originated in the Earth’s lower mantle. Reported here are the results from new experiments producing fPc-bearing assemblages at 20–24 GPa and 1800–2000°C, and the observations are explained with an analysis of the relevant phase relations. These results suggest that some fPc inclusions could have originated at the base of the transition zone, if the mantle temperatures were higher than 1800°C. In this case, a reaction of garnet with fPc could cause a seismic discontinuity near 660 km.